2020
DOI: 10.1111/mcn.13046
|View full text |Cite
|
Sign up to set email alerts
|

Dietary adequacy and nutritional status of Meitei community of Manipur, Northeast India

Abstract: Meitei is the main ethnic community that belongs to the north‐eastern state of Manipur in India. This community is bestowed with rich biodiverse resources with indigenous foods still form an integral part of their diet. However, limited data on the food and nutrient consumption as well as nutritional status of this community are available. This study was carried out on the children, adolescents and women of reproductive age (WRA) of this community from 12 villages, to determine their food consumption pattern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The intake of calcium was excessively lower among women of Zambia (146 mg) (Kaliwile et al., 2019 ), and South Africa (150.5 mg) (Oldewage‐Theron & Kruger, 2011 ), Ethiopia (302.6 mg) (Asayehu et al., 2017 ), and Bangladesh (161.56–323.6 mg) (Akter et al., 2021 ; Arsenault et al., 2013 ; Islam et al., 2021 ; Sultana et al., 2019 ). Only a study in India (905 mg) (Loukrakpam et al., 2020 ) showed adequate intake of calcium among the women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intake of calcium was excessively lower among women of Zambia (146 mg) (Kaliwile et al., 2019 ), and South Africa (150.5 mg) (Oldewage‐Theron & Kruger, 2011 ), Ethiopia (302.6 mg) (Asayehu et al., 2017 ), and Bangladesh (161.56–323.6 mg) (Akter et al., 2021 ; Arsenault et al., 2013 ; Islam et al., 2021 ; Sultana et al., 2019 ). Only a study in India (905 mg) (Loukrakpam et al., 2020 ) showed adequate intake of calcium among the women.…”
Section: Resultsmentioning
confidence: 99%
“…The intake of daily dietary iron by the women in LMICs (3.8–36.0 mg) was above the daily EAR of 15 mg. The studies in Ethiopia (36.0 mg) (Asayehu et al., 2017 ), Vietnam (15.5 mg) (Nguyen et al., 2014 ), Congo (18.8–20.3 mg) (Moumin et al., 2020 ), Nigeria (16.8 mg) (De Moura et al., 2015 ), and India (22.3 mg) (Loukrakpam et al., 2020 ) indicated that dietary iron intake was satisfactory compared to the EAR. On the other hand, studies in Lebanon (8.0 mg) (Abou‐Rizk et al., 2021 ), India (7.39 mg) (Nunn et al., 2019 ), Zambia (7.39 mg) (Kaliwile et al., 2019 ), and South Africa (3.8 mg) (Oldewage‐Theron & Kruger, 2011 ), and Bangladesh (6.72–11.63 mg) (Akter et al., 2021 ; Arsenault et al., 2013 ; M. H. Islam et al., 2021 ; Sultana et al., 2019 ) showed lower intake of iron than the recommended EAR.…”
Section: Resultsmentioning
confidence: 99%
“…Reliable estimates from NER on the burden of folate deficiency during pregnancy are currently unavailable. However, surveys among WRA from different communities in NER have documented low intakes of dietary folate ( 41 , 42 ). Interestingly, the recent Comprehensive National Nutritional Survey found preponderance of folate deficiency among adolescents from NER ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…We note a higher burden of stunting in rural Meghalaya and Sikkim, and severe/wasting in rural Tripura and urban Nagaland. Manipur had one of the lowest prevalence of malnutrition indicators in NE states and this could be attributed to the better socioeconomic status of the population [ 30 ]. Conversely, high stunting in Meghalaya—primarily driven by Khasi Hill tribes—can be linked with high food insecurity, low income, and over-reliance on commercial agricultural products and food provided through Public Distribution System [ 15 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest equipping community healthworkers in identifying and counselling overnutrition cases in addition to undernutrition. Past literature, including a study on the Meitei tribe of Manipur, have found associations of childhood overweight with consumption of energy-dense or sugary food, sedentary lifestyle [ 40 ], lack of dietary diversity, maternal overweight, smoking, no breastfeeding and rapid urbanisation [ 30 , 41 ].…”
Section: Discussionmentioning
confidence: 99%